KEBERFUNGSIAN KELUARGA TERHADAP KENAKALAN REMAJA DI SMP X SELOREJO - Sheila Wardatu Sari; Udi Rosida Hijrianti (Jurnal EMPATI, 2024)
Juvenile delinquency is an act against the law in the family, school, and community. One of the factors causing juvenile delinquency is family dysfunction. This research aims to determine the influence of family functioning on juvenile delinquency among students at SMP X Selorejo. This research uses a quantitative approach. The data collection method uses percentage stratified sampling. The subjects of this research were 175 students of SMP X Selorejo. The measuring instruments used are the Family Assessment Device (FAD) and the juvenile delinquency scale. The research results using simple regression analysis techniques show a value of p=0.001 (<0.05) with a contribution value of 7.7% to family functioning towards juvenile delinquency. The conclusion of the hypothesis is accepted, namely that there is a role for family functioning in juvenile delinquency at SMP X Selorejo students; therefore, it is hoped that family members will improve family functioning.